BOER BUCK SPERM QUALITY IN EXTENDER SUPPLEMETED WITH NON-ENZYMATIC ANTIOXIDANTS AND STORAGE AT COLD TEMPERATURE - Zaenuri, Lalu; Rodiah, R; Dradjat, Adji Santoso; HY, Lukman; Yuliani, Eny (Universitas Syiah Kuala, 2023)
The aim of this study was to determine the durability of standard extender tris egg yolk supplemented with non-enzymatic antioxidants from guava and fig fruit filtrate on the motility and viability of Boer buck sperm. Semen was collected using an artificial vagina every four days for ten replications. The treatment extenders were Tris+2.5% egg yolk (P0) and P0+1.487 mg vitamin A and P0+3.958 mg vitamin C per ml/100 ml (v/v) hereinafter referred as P1 and P2, respectively. The experimental design was a completely randomized 3 times 10 a factorial pattern. The variables assessed were individual motility, progessive motility and viability of sperm evaluated every day for 4 consecutive days. Result indicated that, 4 days after extended and stored at 5C, the average individual motility, progessive motility and sperm viability were 45.27.94; 33.010.2 and 49.67.69 for P1, and 45.46.14; 30.48.38 and 50.55.88 for P2. The data on the three indicators of sperm quality between P1 and P2 did not show a significant difference (P0.05). While for P0 30.65.85; 24.67.30 and 40.75.77, respectively, and were significantly lower (P 0.05) than P0 or P1. It was concluded that semen extended using tris-egg yolk extender supplemented with vitamin A or C could still be used for Artificial Insemination until day 4 after extended and storage at 5C. It is suggested that research needs to be done to produce a ready to use, simple preaparation, cheap and long lasting instant extender.